2015
DOI: 10.1002/maco.201508701
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical characterization and corrosion behavior of an Fe‐Mn‐Si shape memory alloy in simulated concrete pore solutions

Abstract: The corrosion behavior of an Fe‐17Mn‐6Si‐10Cr‐4Ni‐1(V,C) shape memory alloy was investigated using electrochemical methods with regard to its applications as reinforcing element in pre‐stressed concrete structures. The alloy was tested in three kinds of simulated concrete pore solutions, and open circuit potential and linear polarization resistance were monitored with and without chloride addition. The results were compared with a reference material of conventional structural steel, so called S500 (EN 10149 PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…This alloy has been designed for use in civil engineering and therefore has comparably low transformation temperatures [18]. It has been studied extensively with regard to its microstructure, shape memory properties with a special emphasize on shape recovery stresses under mechanical constraints, static and cyclic materials properties and corrosion behavior [26][27][28][29]. The goals of the present study are to describe the influence of carbide precipitates on the fcc to hcp transformation for this particular master alloy composition, to study the fcc to hcp transformation as a function of the grain orientation and potentially resulting load transfers between different grain families and to shed light on the general microstructural mechanisms of pseudo-elasticity.…”
Section: X-ray and Neutron Diffraction Provide Phase Selective Informmentioning
confidence: 99%
“…This alloy has been designed for use in civil engineering and therefore has comparably low transformation temperatures [18]. It has been studied extensively with regard to its microstructure, shape memory properties with a special emphasize on shape recovery stresses under mechanical constraints, static and cyclic materials properties and corrosion behavior [26][27][28][29]. The goals of the present study are to describe the influence of carbide precipitates on the fcc to hcp transformation for this particular master alloy composition, to study the fcc to hcp transformation as a function of the grain orientation and potentially resulting load transfers between different grain families and to shed light on the general microstructural mechanisms of pseudo-elasticity.…”
Section: X-ray and Neutron Diffraction Provide Phase Selective Informmentioning
confidence: 99%
“…However, the chloride concentration in seawater can be up to 0.6 M, which is why HRB400 steel cannot be directly used in seawater concrete. When the concentration of chloride is between 0.1 and 0.2 M, the passive film initially formed on the surface of the steel rebar is unstable and may lead to pitting corrosion in the future . Therefore, the tolerance threshold of steel rebar to mixed‐in chloride during the concrete curing stage is only 0.05 M. Limiting the concentration of mixed‐in chloride ions in curing concrete to no more than 0.05 M is a reasonable guideline for applying HRB400 steel in marine sand concrete.…”
Section: Resultsmentioning
confidence: 99%
“…The recovery stress ranging from 130 to 580 MPa has been reported with various heating temperatures between 130 and 580 °C on different Fe-SMAs [ 11 ]. It has been shown that Fe-SMA has good fatigue [ 12 ] and corrosion resistance [ 13 ], making it even more attractive in structural applications.…”
Section: Introductionmentioning
confidence: 99%